EFEITO DA DENSIDADE DE PLANTAS SOBRE O COMPORTAMENTO DE DOIS CULTIVARES DE SOJA - Nakagawa, JoÃ£o; Rosolem, Ciro Antonio; Machado, JosÃ© Ricardo (REVISTA DE AGRICULTURA, 2015)
EFEITO DA DENSIDADE DE PLANTAS SOBRE O COMPORTAMENTO DE DOIS CULTIVARES DE SOJA